Tradisi Pecah Kendi Pada Masyarakat Suku Jawa Di Kecamatan Brandan Barat - Ramadhani Fahlevi (Journal Smart Law, 2023)
One of the customs in marriage in Indonesia, namely in Javanese traditional weddings, one of the series of wedding ceremonies in the customs of this tribe is Pecah Kendi. The custom of Pecah kendi is a culture of the Javanese ethnicity which continues to be maintained and preserved. As happened in the village of Sei Tualang, Brandan Barat District, the meaning of breaking a jug is to open the door of sustenance for those who do it. The tradition of breaking kendi in this village has taken root, especially for Javanese people who are getting married. The breaking of the jug is carried out after the marriage ceremony is held when the bride and groom meet (nemokkan). From this background, it is deemed necessary to conduct research related to the tradition of breaking the jug in marriage, especially regarding the practice that occurred in Sei Tualang Village, Brandan Barat District. This study aims to determine the tradition of breaking the jug at marriage in Sei Tualang Village, Brandan Barat District, the background of this tradition, and the Langkat MUI's opinion regarding it. The type of research used is field research with a qualitative approach. The data were collected using interview and observation techniques, with primary data sourced from interviews with the Langkat MUI, supported by secondary data sourced from relevant studies. Data analysis is done by organizing data, synthesizing, compiling into patterns, and making conclusions. The results of his research are: first, the tradition of breaking a jar in Brandan Barat District uses certain materials and stages which all have meaning; second, the roots of this tradition are the reason why this tradition cannot be separated from weddings; third, the Langkat MUI allows this tradition if it does not conflict with sharia, and prohibits it if it does.